Faktor-Faktor yang Berpengaruh terhadap Kejadian Tuberkulosis pada Wanita (Studi Kasus di RSUD Kabupaten Brebes) - Muslih Muslih; Djoko Tri Hadi Lukmono; Suhartono Suhartono; Ari Suwondo; Martini Martini (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2018)
Background: Tuberculosis (TB) risk in women increased during the productive age. Various problems can arise if a woman suffering from TB given the role of women, especially married, pregnant, and have children. Her role as a housewife who must carry out the task of physical and mental care of children at the same time taking care of her husband will be disrupted. To determine the chances of marital status, pregnancy, parity, physical activity, level of education, level of knowledge, the kitchen smoke pollution, household contact history, history of comorbidities DM, population density, and spacious house ventilation of TB incidence in women.Methods: The study was observational analytic study with case control design. The sample size is as much as 128 people, consisting of 64 cases and 64 controls. Sampling was done by proportional random sampling technique. Data were analyzed with univariable, bivariable, and multivariable.Results: The results of multivariate analysis, parity (OR 5.9, 95% CI 2.40-14.89, p 0.0001), contact history (OR 4.9, 95% CI 1.75-14.14, p 0.003), pollution kitchen smoke (OR 4.2, 95% CI 1.71-10.67, p 0.002), ventilation (OR 4.2, 95% CI 1.72- 10.44, p 0.002) as a risk factor for TB in women.Conclusion: The incidence of tuberculosis in women in Brebes chance or greater risk inwomen with high parity, a history of contacts, exposure to cooking smoke pollution is high and stay at home with ventilation that do not qualify health requirements.